Methods for Combating Transnational Crime in Indonesia - Liana, Nora; Ade Ira Octa Femi; Ricky Rosiwa; Rifki Mulia (International Journal of Law, Social Science, and Humanities, 2025)
Transnational crime is a serious challenge for Indonesia, considering its strategic geographical position and its role in international trade routes. This research aims to evaluate methods for dealing with transnational crime in Indonesia and their effectiveness. The methodology used is a qualitative approach with data analysis from in-depth interviews, case studies, and official documents from law enforcement agencies. The research results show that Indonesia has implemented various strategies, such as increasing international cooperation, strengthening regulations, and training for law enforcement officers. However, challenges remain in terms of human resources, infrastructure and corruption. This research recommends the need for a holistic approach involving civil society and increased transparency in the law enforcement system to tackle transnational crime more effectively.